The androgen-dependent C4-Slp gene is driven by a constitutively competent promoter. - Miyagoe, Y (1993)
The androgen-dependent liver protein Slp, together with its constitutively expressed closely related isoform C4, provides a model to address the question of which minimal alteration in DNA can shut off the expression of a gene in a manner reversible by testosterone or by trans-acting mutations. Previous work indicated that sequences located at -1.9, -0.45, and -0.25 kb from the transcription start site of the C4-Slp gene played a critical role in determining its unusual functional divergence from C4. Now, using quantitatively and qualitatively controlled transfection assays in HepG2 human hepatoma cells and mouse L fibroblasts, we have observed that the C4-Slp promoter is fully effective and unhindered by upstream sequences and that the C4 promoter has a consistent albeit modest superiority. The determinant of this nearly 2-fold difference does not coincide with the sites highlighted in previous studies but lies within the most cap-site-proximal nucleotides, at positions -189 to +48. We have also established conditions for cell-free transcription of C4 and C4-Slp from plasmid and cosmid templates by using nuclear extracts from rat and mouse liver of both sexes as well as from L cells. At variance with the rat alpha 2u-globulin gene, C4-Slp transcription in vitro does not require male factors, for it is expressed as efficiently as C4 by all nuclear extracts. Further, the minimal promoter sequences required to direct accurate initiation extend not farther than the most proximal 19 nucleotides. Because L cells efficiently express transfected cosmids covering the whole C4 gene or C4/C4-Slp recombinants, as well as plasmids carrying the C4-Slp promoter, but fail to express the full C4-Slp gene, we favor a model in which the expression of the gene is modulated intragenically.